2021
DOI: 10.1101/2021.11.13.468478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Poly ADP-ribosylation of SET8 leads to aberrant H4K20 methylation in mammalian nuclear genome

Abstract: In mammalian cells, SET8 mediated Histone H4 Lys 20 monomethylation (H4K20me1) has been implicated in regulating mitotic condensation, DNA replication, DNA damage response, and gene expression. Here we show SET8, the only known enzyme for H4K20me1 is post-translationally poly ADP-ribosylated by PARP1 on lysine residues. PARP1 interacts with SET8 in a cell cycle- dependent manner. Poly ADP-ribosylation on SET8 renders it catalytically compromised and it undergoes degradation via ubiquitylation pathway. Knockdow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 87 publications
(100 reference statements)
0
2
1
Order By: Relevance
“…S4-5), indicating that PARP-1 is not directly implicated in the regulation of pr-set7. This finding contrasts with recent evidence demonstrating PARP1-induced degradation of PR-SET7/SET8 in human cells (16).…”
Section: Parp-1 and Pr-set7 Co-regulate Developmental Gene Expression...contrasting
confidence: 99%
See 2 more Smart Citations
“…S4-5), indicating that PARP-1 is not directly implicated in the regulation of pr-set7. This finding contrasts with recent evidence demonstrating PARP1-induced degradation of PR-SET7/SET8 in human cells (16).…”
Section: Parp-1 and Pr-set7 Co-regulate Developmental Gene Expression...contrasting
confidence: 99%
“…A recent study demonstrated that in human cells overexpressing PARP-1, PR-SET7/SET8 is degraded, whereas depletion of PARP-1 leads to an increase in PR-SET7/SET8 levels (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation